KAJIAN YURIDIS HAK WARIS ANAK ANGKAT BERDASARKAN WASIAT ORANG TUA ANGKAT DITINJAU DARI KUHPERDATA - Nazhifa Salsabiela; H. Israfil Israfil (Fakultas Hukum Universitas Mataram, 2021)
The purpose of this study was to determine the position of adopted children in inheritance in terms of the Civil Code and to determine the distribution of children's inheritance rights seen from the Civil Code. This research is normative juridical by using invitation approach and conceptual approach. The results of this study are the position of adopted children in inheritance is different from biological children, adopted children get inheritance through a will. the distribution of the inheritance rights of adopted children in civil law can be done by testament and there is no limit on the share of the adoptive parents to inherit their property as long as it does not conflict with the legitime portie